S7 Influence of Beta-2 Adrenoceptor Genotype on Response to Regular Racemic or Levosalbutamol in Steroid Treated Asthmatics. (19th November 2012) - Anderson, WJ; Short, PM; Williamson, PA; Morrison, AE; Palmer, CNA; Tavendale, R; Lipworth, BJ
Abstract : Background: Asthmatic patients receiving inhaled corticosteroids often take frequent add-on therapy with albuterol despite on-demand prescription. We wished to evaluate trough methacholine airway hyper-responsiveness (the primary outcome) following regular treatment with racemic salbutamol and levosalbutamol compared to placebo, in steroid treated asthmatics stratified according to beta-2 adrenoceptor 16 genotype. Methods: We performed a randomised, double-blind, placebo-controlled, triple crossover trial comparing 2 weeks of regular therapy with inhaled racemic salbutamol (200µg qid); levosalbutamol (100µg qid); or placebo on methacholine PC20 6 hours post dose in 30 persistent asthmatics (15 homozygous Arg16 and Gly16) receiving inhaled corticosteroids. Results: There was no rebound worsening of trough airway hyper-responsiveness to methacholine after chronic exposure to either racemic (p=0.53) or levosalbutamol (p=0.84) compared to placebo; nor between genotypes - as doubling dilution (dd) difference in methacholine PC20 from placebo (Figure 1 ): salbutamol/Arg16= 0.36dd (95% CI: –0.43, 1.15); salbutamol/Gly16=0.01dd (95% CI: –0.47, 0.49); levosalbutamol/Arg16=–0.01dd (95% CI: –0.89, 0.87); levosalbutamol/Gly16=0.28dd (95% CI: –0.22, 0.77). Both active treatments improved morning PEF in Gly16 (p=0.04) but not Arg16 patients (p=0.50); while evening PEF improved in both Gly16 (p<0.001) and Arg16 patients (p=0.006). Conclusions: Chronic exposure to either racemic or levosalbutamol added to inhaled corticosteroids did not cause rebound worsening of airway hyper-responsiveness at trough compared to placebo; with no difference seen between beta-2 adrenoceptor 16 genotypes.